The Role of Sentience in the Theory of Consciousness and Medical Practice - Pereira Jr, Alfredo [UNESP] (Imprint Academic, 2021)
In this target paper, I focus on the concept of sentience in relation to the theory of consciousness and to practice in the medical sciences, neurology, and psychiatry, regarding both diagnostics and therapy. Following authors in this field, I distinguish two modalities of consciousness: sentience, in the sense of being awake and capable of feeling (e.g. basic sensations of hunger, thirst, pain) and, second, cognitive consciousness, i.e. thinking and elaborating on linguistic and imagery representations. The physiological correlates of sentience are proposed to be the systems underpinning the dynamic control of biochemical homeostasis, while the correlates of cognitive consciousness are considered to be patterns of bioelectrical activity in neural networks. I claim that sentience needs to be taken in account if better tools are to be developed for medical diagnostics (e. g. by identifying biochemical markers) and therapy (e.g. using new drugs and brain stimulation technologies targeting the correlates of sentience). The main hypothesis presented here to support this claim is that cognitive consciousness depends on sentience, but not vice versa, implying that medical practice should also address the physiological correlates of sentience in the diagnostics and therapy of disorders of consciousness.
Keywords: sentience; consciousness; glial cells; homeostasis; allostasis; neurology; psychiatry